2017
DOI: 10.1016/j.biocon.2017.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Designing cost-effective capture-recapture surveys for improving the monitoring of survival in bird populations

Abstract: NB species, focusing the NB rounds at a period that maximises the chance to capture breeding females inside nest-boxes is more rewarding than ringing all chicks. We show that integrating economic costs is crucial when designing CR surveys and discuss ways to improve efficiency by reducing duration to a time scale compatible with management and conservation issues.3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 38 publications
(37 reference statements)
1
13
0
1
Order By: Relevance
“…Few studies achieve complete detection and therefore multiple sampling occasions are required in order to minimise any associated biases (Lebreton et al 1992). In agreement, our analyses demonstrated that the accuracy of survival estimation, and the ability to detect sources of variation were improved greatly when time series were extended (also see Lieury et al 2017). Our study also demonstrated that in longer survey designs, the estimation of adult survival rates was only marginally improved by conducting mark-recapture field studies that target both adults and chicks, as opposed to adults only.…”
Section: Discussionsupporting
confidence: 80%
“…Few studies achieve complete detection and therefore multiple sampling occasions are required in order to minimise any associated biases (Lebreton et al 1992). In agreement, our analyses demonstrated that the accuracy of survival estimation, and the ability to detect sources of variation were improved greatly when time series were extended (also see Lieury et al 2017). Our study also demonstrated that in longer survey designs, the estimation of adult survival rates was only marginally improved by conducting mark-recapture field studies that target both adults and chicks, as opposed to adults only.…”
Section: Discussionsupporting
confidence: 80%
“…unmarked individuals, dead recoveries) into OPSCR models could help further mitigate the negative impact of interruptions on the precision of parameter estimates (see Chandler and Clark (2014) for an example). Previous studies testing the cost-efficiency of non-spatial CR surveys have focused on the importance of study duration, proportion of different individuals sampled, and detection probability (Lieury et al 2017). Unless the study species requires close monitoring due to short response times for management interventions (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the presented approach could be adapted to consider the time variations of the force of infection to account for epidemic cases or to incorporate parameters to account for a potential disease-induced mortality (discussed in Appendix S1: Section S1). In contrast, if the main interest is on the survival probability, putting more effort on resighting (independently of recapture) could improve the precision of the estimates (Lahoz-Monfort et al 2014, Lieury et al 2017), but integrating cross-sectional data will provide no added benefit (Appendix S1: Fig. The sampling design will of course have to be adapted to the main objective of the survey (Yoccoz et al 2001).…”
Section: Fig 2 Continuedmentioning
confidence: 99%
“…S6b, top panel). In contrast, if the main interest is on the survival probability, putting more effort on resighting (independently of recapture) could improve the precision of the estimates (Lahoz-Monfort et al 2014, Lieury et al 2017), but integrating cross-sectional data will provide no added benefit (Appendix S1: Fig. S6a, middle panel).…”
Section: Fig 2 Continuedmentioning
confidence: 99%